Students’ Perceptions Of Kahoot-Based Speaking Activities In Efl Classrooms: A Narrative Literature Review - M. Dhava Sa’dit Daroiny; Nailul Authar; Tiyas Saputri; Savira Zaniar (Edu Journal Innovation in Learning and Education, 2026)
The integration of gamification into English as a Foreign Language (EFL) instruction has gained significant attention due to its potential to increase student engagement and motivation. Among various digital learning platforms, Kahoot has emerged as one of the most widely used tools for creating interactive and game-based learning experiences. While numerous studies have investigated the effectiveness of Kahoot in improving learning outcomes, limited attention has been paid to students’ perceptions of its use in speaking activities. This narrative literature review aims to explore how students perceive Kahoot-based speaking activities and to identify the pedagogical benefits and challenges associated with its implementation in EFL classrooms. The review synthesizes findings from recent studies published between 2016 and 2025 focusing on Kahoot, speaking instruction, gamification, and learner engagement. The findings indicate that students generally perceive Kahoot positively due to its ability to create an enjoyable learning atmosphere, reduce speaking anxiety, increase motivation, and encourage classroom participation. Furthermore, Kahoot facilitates collaborative interaction and promotes willingness to communicate in English. However, several challenges have also been identified, including time pressure, technological limitations, and the possibility of prioritizing competition over meaningful communication. The review concludes that Kahoot has considerable potential to support speaking activities when integrated with communicative teaching strategies. Future research is encouraged to investigate long-term impacts of Kahoot on speaking development and communicative competence in diverse EFL contexts.